The vanished world of Lithuanian Jews - Schreiner, Stefan; Staliūnas, Darius; Nikžentaitis, Alvydas (On the boundary of two worlds, 2004)
Traditions of the Commonwealth: Lithuanian Jewry and the exercise of political power in tsarist Russia /John D. Klier --Changes in the political pituation and the "Jewish question" in the Lithuanian Gubernias of the Russian empire (1855-April 1863) /Darius Staliūnas --Politics, society, and antisemitism: peculiarities of the Russian empire and Lithuanian lands /Theodore R. Weeks --Notes on the origin and development of modern Lithuanian antisemitism in the second half of the nineteenth century and at the beginning of the twentieth century /Vladas Sirutavičius --Some remarks on the Jewish condition in interwar east central Europe /Ezra Mendelsohn --Expressions of Litvak pro-Lithuanian political orientation c. 1906-c.1921 /Eglè Bendikaitè --Lithuanian general aspects of domestic policy 1918-1940 /Česlovas Laurinavičius --The historical sources for antisemitism in Lithuania and Jewsih-Lithuanian relations during the 1930s /Saulius Sužiedèlis --State and minorities. The first Lithuanian republic and S.M. Dubnov's concept of cultural autonomy /Verena Dohrn --The murder of the Jews in German-occupied Lithuania (1941-1944) /Yitzhak Arad --The Holocaust in Lithuania: an outline of the major stages and their result /Arūnas Bubnys --Holocaust and musar for the Telšiai yeshivah: Avraham Yitshak and Eliyahu Meir Bloch /Gershon Greenberg --The Holocaust in the western regions of Belarus /Yevgeni Rozenblat --Lithuanian participation in the mass murder of Jews in Belarus and Ukraine (1941-1944) /Martin C. Dean --Coming to terms with a difficult past /Joachim Tauber.